BROWNIES BERBAHAN TEPUNG UBI UNGU, TEPUNG KEDELAI, DAN BIJI CHIA (BROWTASOY) SEBAGAI MAKANAN SELINGAN UNTUK PASIEN DM TIPE 2 - Ayunastity, Azmi Ajeng; Fitria, Mona; Saleky, Yohannes Willihelm; Judiono (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
The form of nutritional therapy for people with DM is dietary management with three meals a day and snacks. Snacks for DM contain carbohydrate levels of 15-30 grams, balanced nutrition, low glycemic index, high fibre and high antioxidants can reduce the rate of glucose absorption and increase insulin sensitivity. The study aimed to determine the effect of different formulations of purple sweet potato flour, soy flour and chia seeds on the quality (organoleptic properties, macronutrient content, fibre and antioxidants) of brownies as a side dish for patients with type 2 diabetes. The research design was experimental involving 30 moderately trained panellists. Data normality test using Shapiro Wilk with data not normally distributed, then the analysis uses Kruskal Wallis test. The results showed that there was an effect of the formulation of purple sweet potato flour, soy flour and chia seeds on the quality of the brownie formula from the aspects of taste (p=0.041), aroma (p=0.031), texture (p=0.002) and overall (p=0.000) but there was no significant effect on the colour aspect (p=0.330). Formula 1 with the addition of 60% purple sweet potato flour, 30% soya flour and 10% chia seeds was the best formula favoured by panellists with a hedonic score of 5.9. Browtasoy product test results in the laboratory showed 188.5 Kcal energy, 4 g protein, 13.5 g fat, 12.5 g carbohydrate and 2.5 grams of fibre and antioxidant activity of 255.245 ppm (moderate antioxidant activity) per 50 gram serving. The production cost price of 50 g serving is Rp. 12,643.56. It is necessary to develop a better formula in nutritional value by modifying ingredients to increase protein and carbohydrate levels and reduce product fat content.